Characteristics of Adult Sepsis Patients Admitted to Department of Internal Medicine, Dr. M. Djamil General Hospital, Padang, Indonesia - Elvia Fataya; Fadrian; Mustafa Noer; Dwitya Elvira; Yuliarni Syafrita; Netti Suharti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Sepsis is a life-threatening organ dysfunction resulting from a dysregulated host response to infection. Septic shock is the most dangerous complication of sepsis, characterized by abnormalities in the circulatory and metabolic systems. This study aimed to determine the characteristics of adult sepsis patients admitted to the department of internal medicine of Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This research was a descriptive study and used secondary data from medical records. Samples in this study were medical record data from the medical record installation of Dr. M. Djamil General Hospital, Padang, Indonesia. The inclusion criteria were adult patients aged more than 18 years old, diagnosed with sepsis, and hospitalized in the department of internal medicine for the period of January 2020 to December 2021. Results: Most of the sepsis patients were mostly aged more than 60 years old (51.7%), female (57.2%), and had normal BMI scores (59.3%). The infections mainly originated from the lungs (80%), the most common comorbid disease was chronic kidney disease (26.4%), the most frequent causing microorganism was Escherichia coli (15.9%), the frequent degree of severity was a septic shock (60%), and cefepime was used as the initial empirical antibiotic (44.8%). Conclusion: Most sepsis patients were adults aged more than 60 years old and females, with the focus on infection originating from the lungs, degree of severity in the form of septic shock, and the most used initial empirical antibiotic, namely cefepime.